Implementation of 6-DOF Biped Footstep Planning Under Different Terrain Conditions - Senthil Kumaran, B; J.Jebasingh Kirubakaran, S (International Journal of Engineering and Technology, 2018)
Humanoid robots gain starting their anthropomorphic profile when functional in human-made environments. In direct to achieve human-like capabilities, robots must be able to recognize, understand and interrelate with the nearby world. We present the development of safe routing strategy for biped robots moving in difficulty untidy environments. In the near view, humanoids play a vital role in helping the mankind by performing the day today activities. Navigation of a humanoid under different terrain conditions such as flat, inclined and slippery environments is a challenge that requires a solution to use humanoids in the households. In this regard, in the planned paper work, a biped robot with 6-Degree of freedom has been designed and tested on the sloped and slippery surfaces, in addition to it, the ultrasonic sensors are used to identify the obstacles. Based on the obstacle identification, the biped path can be altered in order to evade impact within obstacle. Â Â Â